Motivating style, basic psychological needs, motivation, vitality and exhaustion in school athletes - Rodriguez, José (2025)
Practicing a competitive sport at a school age can be a positive development factor however, it may also be an experience of pressure and stress for the athlete. Supporting the athlete from a young age is extremely important to have an optimal motivation. Based in Self-determination Theory (SDT) the present study investigated the relationship between coaches’ motivational style (autonomy support, control), the satisfaction and frustration of basic psychological needs (BPNs), the motivation of the athlete, subjective vitality and physical and emotional exhaustion. The presence of a “bright-path” (adaptive) and a “dark-path” (maladaptive) of motivation was hypothesized. Questionnaires were applied to a sample of 118 school athletes from Metropolitan Lima and the hypothetical model based on SDT was inspected through path analysis. It was found that greater perceived autonomy support by the athletes with respect to their coaches predicted a greater satisfaction of the BPNs, greater autonomous motivation and greater subjective vitality. On the contrary, the greater the control by the coach, the greater the frustration of psychological needs and control motivation and lesser vitality. Important motivational aspects for athletes of younger ages based on SDT are discussed.